Antarctic environmental protection: strengthening the links between science and governance - Hughes, Kevin A; Constable, Andrew; Frenot, Yves; López-Martinez, Jerónimo; McIvor, Ewan; Njåstad, Birgit; Terauds, Aleks; Liggett, Daniela; Roldan, Gabriela; Wilmotte, Annick; Xavier, José C (Environmental Science & Policy, 2018)
The Antarctic has significant environmental, scientific, historic, and intrinsic values, all of which are worth protecting into the future. Nevertheless, the area is subject to an increasing level and diversity of human activities that may impact these values within marine, terrestrial and cryosphere environments. Threats to the Antarctic environment, and to the aforementioned values, include climate change, pollution, habitat destruction, wildlife disturbance and non-native species introductions. Over time, a suite of legally binding international agreements, which form part of the Antarctic Treaty System (ATS), has been established to help safeguard the Antarctic environment and provide a framework for addressing the challenges arising from these threats. Foremost among these agreements are the Protocol on Environmental Protection to the Antarctic Treaty and the Convention on the Conservation of Antarctic Marine Living Resources. Many scientists working in Antarctica undertake research that is relevant to Antarctic environmental policy development. More effective two-way interaction between scientists and those responsible for policy development would further strengthen the governance framework, including by (a) better communication of policy makers’ priorities and identification of related science requirements and (b) better provision by scientists of ‘policy-ready’ information on existing priorities, emerging issues and scientific/technological advances relevant to environmental protection. The Scientific Committee on Antarctic Research (SCAR) has a long and successful record of summarizing policy-relevant scientific knowledge to policy makers, such as through its Group of Specialists on Environmental Affairs and Conservation (GOSEAC) up to 2002, currently the SCAR Standing Committee on the Antarctic Treaty System (SCATS) and recently through its involvement in the Antarctic Environments Portal. Improvements to science-policy communication mechanisms, combined with purposeful consideration of funding opportunities for policy-relevant science, would greatly enhance international policy development and protection of the Antarctic environment.
Keywords: Antarktis; miljøvern

The retrospective analysis of Antarctic tracking data project - Ropert-Coudert, Yan; Van de Putte, Anton P; Reisinger, Ryan R; Bornemann, Horst; Charrassin, Jean-Benoît; Costa, Daniel P; Danis, Bruno; Hückstädt, Luis A; Jonsen, Ian D; Lea, Mary-Anne; Thompson, David; Torres, Leigh G; et al. (Scientific Data, 2020)
The Retrospective Analysis of Antarctic Tracking Data (RAATD) is a Scientific Committee for Antarctic Research project led jointly by the Expert Groups on Birds and Marine Mammals and Antarctic Biodiversity Informatics, and endorsed by the Commission for the Conservation of Antarctic Marine Living Resources. RAATD consolidated tracking data for multiple species of Antarctic meso- and top-predators to identify Areas of Ecological Significance. These datasets and accompanying syntheses provide a greater understanding of fundamental ecosystem processes in the Southern Ocean, support modelling of predator distributions under future climate scenarios and create inputs that can be incorporated into decision making processes by management authorities. In this data paper, we present the compiled tracking data from research groups that have worked in the Antarctic since the 1990s. The data are publicly available through biodiversity.aq and the Ocean Biogeographic Information System. The archive includes tracking data from over 70 contributors across 12 national Antarctic programs, and includes data from 17 predator species, 4060 individual animals, and over 2.9 million observed locations.
Keywords: Antarktis; Sørishavet; biologi; økologi; økosystem

Tracking of marine predators to protect Southern Ocean ecosystems - Hindell, Mark A; Reisinger, Ryan R; Ropert-Coudert, Yan; Hückstädt, Luis A; Trathan, Philip N; Bornemann, Horst; Charrassin, Jean-Benoît; Chown, Steven L; Costa, Daniel P; Danis, Bruno; Lea, Mary-Anne; Thompson, David; et al. (Nature, 2020)
Southern Ocean ecosystems are under pressure from resource exploitation and climate change1,2. Mitigation requires the identification and protection of Areas of Ecological Significance (AESs), which have so far not been determined at the ocean-basin scale. Here, using assemblage-level tracking of marine predators, we identify AESs for this globally important region and assess current threats and protection levels. Integration of more than 4,000 tracks from 17 bird and mammal species reveals AESs around sub-Antarctic islands in the Atlantic and Indian Oceans and over the Antarctic continental shelf. Fishing pressure is disproportionately concentrated inside AESs, and climate change over the next century is predicted to impose pressure on these areas, particularly around the Antarctic continent. At present, 7.1% of the ocean south of 40°S is under formal protection, including 29% of the total AESs. The establishment and regular revision of networks of protection that encompass AESs are needed to provide long-term mitigation of growing pressures on Southern Ocean ecosystems.
Keywords: Sørishavet; klimaendringer; marin biologi; marine økosystemer; miljøvern; overvåking